Packaging for Sustainability - Verghese, Karli; Lewis, Helen; Fitzpatrick, Leanne; SpringerLink (Online service) (London : Springer London, 2012)
The packaging industry is under pressure from regulators, customers and other stakeholders to improve packaging$1 (Bs sustainability by reducing its environmental and societal impacts. This is a considerable challenge because of the complex interactions between products and their packaging, and the many roles that packaging plays in the supply chain. Packaging for Sustainability is a concise and readable handbook for practitioners who are trying to implement sustainability strategies for packaging. Industry case studies are used throughout the book to illustrate possible applications and scenarios. Packaging for Sustainability draws on the expertise of researchers and industry practitioners to provide information on business benefits, environmental issues and priorities, environmental evaluation tools, design for environment, marketing strategies, and challenges for the future.s
1. Developing the Strategy -- 2. Designing for Sustainability -- 3. Marketing and Communicating Sustainability -- 4. Complying with Regulations -- 5. Applying Life Cycle Assessment -- 6. Packaging Materials -- 7. Selecting and Applying Tools -- 8. Implementing the Strategy.
Keywords: Engineering; Engineering design; Industrial engineering; Waste disposal; Engineering; Industrial and Production Engineering; Waste Management/Waste Technology; Engineering Design; Innovation/Technology Management